2021
DOI: 10.1111/jcpt.13521
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of empagliflozin at different doses in patients with type 2 diabetes mellitus: A network meta‐analysis based on randomized controlled trials

Abstract: What is Known and Objective: As an oral hypoglycaemic drug that significantly reduces cardiovascular risk, empagliflozin is often used in patients with type 2 diabetes mellitus (T2DM). However, the dosage and administration of empagliflozin are still controversial clinically. To determine the most appropriate dose, we performed this network meta-analysis. Methods:We identified randomized controlled trials (RCTs) about empagliflozin from eight databases. We analysed the pharmacodynamics, adverse effects (AEs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…On the other hand, there are two reports of network meta-analyses based on randomized control trials of empagliflozin. Wu et al reported that the reduction of HbA1c by 25 mg empagliflozin was greater than that caused by 10 mg empagliflozin, but this was not a significant difference [25 mg vs. 10 mg: effect size − 0.04%; 95%CI − 0.19 to 0.10)] [ 27 ]. They also reported that the reduction of BW by 25 mg empagliflozin was significantly greater than that caused by 10 mg empagliflozin [25 mg vs. 10 mg: effect size − 0.24 kg; 95%CI − 0.39 to − 0.09)] [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there are two reports of network meta-analyses based on randomized control trials of empagliflozin. Wu et al reported that the reduction of HbA1c by 25 mg empagliflozin was greater than that caused by 10 mg empagliflozin, but this was not a significant difference [25 mg vs. 10 mg: effect size − 0.04%; 95%CI − 0.19 to 0.10)] [ 27 ]. They also reported that the reduction of BW by 25 mg empagliflozin was significantly greater than that caused by 10 mg empagliflozin [25 mg vs. 10 mg: effect size − 0.24 kg; 95%CI − 0.39 to − 0.09)] [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al reported that the reduction of HbA1c by 25 mg empagliflozin was greater than that caused by 10 mg empagliflozin, but this was not a significant difference [25 mg vs. 10 mg: effect size − 0.04%; 95%CI − 0.19 to 0.10)] [ 27 ]. They also reported that the reduction of BW by 25 mg empagliflozin was significantly greater than that caused by 10 mg empagliflozin [25 mg vs. 10 mg: effect size − 0.24 kg; 95%CI − 0.39 to − 0.09)] [ 27 ]. Zaccardi et al reported in the other network meta-analysis that the reduction of HbA1c by 25 mg empagliflozin was greater than that caused by 10 mg empagliflozin, but, as in the above reports, the difference was not significant [25 mg vs. 10 mg: effect size − 0.05%; 95%CI − 0.13 to 0.02)] [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Overall, the safety profile of empagliflozin is well established; it is generally well tolerated, with a low risk of serious adverse events. [2][3][4] The safety profile of empagliflozin is supported by the findings of a recent pooled analysis of 20 randomized clinical trials and four extension studies of patients with T2D. The pooled analysis showed that empagliflozin, at doses of 10 or 25 mg, was well tolerated in patients with T2D and was not associated with a higher rate of confirmed hypoglycemia versus placebo, except in patients receiving concurrent insulin and/or a sulfonylurea (SU).…”
Section: Introductionmentioning
confidence: 93%
“…7 For empagliflozin, current data indicate that urinary tract, but not genital, infections are more frequent compared with placebo, although these events are generally mild to moderate in severity and do not usually lead to treatment discontinuation. [2][3][4][5] Several potential adverse events have been associated with SGLT2 inhibitors following safety signals from case reports and large clinical trials of SGLT2 inhibitors. 3,[8][9][10] These include urinary and genital infection, diabetic ketoacidosis, bone fracture, cancers, and foot and toe amputation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation